Generalized Livelihoods Self-efficacy Scale - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Improving women’s self-efficacy, or their belief in own capabilities to act effectively towards their own goals, is an important and urgent policy goal. The 10-item Generalized Livelihoods Self-efficacy Scale allows us to measure self-efficacy applicable to general economic activities. As opposed to treating it as a generalized personality trait or as a domain-specific construct, it intends to be a measure that is applicable across economic activities and to capture livelihoods in general in low-income contexts. It is designed to capture both control over economic decisions and resources and the ability to engage in economic activities. This tool is suited for surveys run by NSOs, other nationally representative individual- or household-level surveys, and for targeted thematic or impact evaluation surveys designed to understand individuals' agency and decision-making. Other variables you may want to collect alongside this tool include engagement in income-generating activities, individual income, and MAGNET’s goal-setting capacity scale. This data study includes following files. 1. A survey document (including implementation guidelines). 2. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.